Prosthetic joint infection due to Candida parapsilosis in the UK: case report and literature review. - Paul, J; White, S; Nicholls, K; Crook, D (1992)
Candida infection of joint replacements is a rare but increasingly reported phenomenon. A case of Candida parapsilosis prosthetic knee joint infection occurring in the UK is described. Cure followed removal of the prosthesis and treatment, first with a combination of amphotericin and 5-fluorocytosine, then ketoconazole.